Role of Angiogenic Factors in Preeclampsia - Pradhan, P (Nepal Journal of Obstetrics and Gynaecology, 2014)
Preeclampsia, the syndrome of hypertension, proteinuria, edema and hyperuricemia occurring during the last trimester of pregnancy remains one of the great mysteries. Recently gene expression profiling of placental tissue from healthy and preeclamptic women used to see which genes were up or down regulated in preeclamptic patients. Alterations in circulating angiogenic proteins correlated with disease severity, earlier onset of preeclampsia and birth of small for gestational age (SGA) fetus. These findings lend support to the hypothesis that circulating angiogenic proteins may have an important biological role in preeclampsia. DOI: http://dx.doi.org/10.3126/njog.v9i1.11194 NJOG 2014 Jan-Jun; 2(1):71-73